Evaluation of Short Video Implementation in Learning - Nadeak, Sandro Jadi Marulitua; Febriaynto, Priyono Tri; Nirtha, Eva (Graduate Program Magister Manajemen Pendidikan, 2024)
This study aims to evaluate the implementation of short videos in learning. This research is evaluation research using the CIPP model by Stuffbleam. The subject of this study was a grade 4 student of SD Kelayan 1 Bangkalan Madura. The method used is a mix method with a Sequential Explanatory design model, namely the first data collection and analysis are carried out quantitatively and then collected and analyzed qualitatively. Data were collected by giving questionnaires, observations, document study and interviews. Qualitative data were analyzed using the Miles and Huberman analysis model. While quantitative data is analyzed by calculating percentages and categorizing. The results of this study show that in terms of context is very good, the input is very good, the process is very good and the product results are categorized as very good. Thus, it can be concluded that Short Video can be used as a learning medium that is useful and easy to use anywhere and anytime as long as supporting facilities are available so it can improve student’s knowledge and skill. However, teachers also need to anticipate the weaknesses of using short videos in learning, including teacher getting permission from parents and principals, teachers must ensure the availability of facilities such as gadgets and also good internet access in classroom learning, especially for primary students.